A escola que eu quero: um estudo sobre permanência dos professores em uma escola estadual de São Paulo - Castro, Elaine Mathias de (2019)
Considering the worldwide context of low attractivity of teaching, the high rates of teachers dropping out all educational networks in all teaching levels, as well as the high rates of turnover of teacher staff confirmed by the Teacher Turnover Indicator (Indicador de Rotatividade Docente) from INEP, we have aimed at the reverse so that we could understand the phenomenon of teachers permanence at a certain state school in the city of São Paulo. Official documents by the Department of Education of the State of São Paulo, INEP and other research institutes have been analyzed as to find a wider view of the phenomenon of teacher turnover. Theory shows that there is greater permanence of teacher at schools with simpler management (according to the Complexity of Management Index [Índice de Complexidade da Gestão], from INEP), with better infrastructure and in less socially vulnerable areas (ALVES et al, 2004; CASASSUS,2002; FRANCO et al, 2007; LAPO;BUENO, 2003). Which, then, would be the actions implemented at a state school located at the extreme East of the city of São Paulo, a place with high social vulnerability, with over 1800 students, working morning, afternoon and night shifts with mostly high school groups, that would contribute for teachers’ preference of it? This qualitative study has used reflexive interviews with seven teachers from the school, principal and vice-principal included, for collecting data, which have been analyzed following the empiric-comprehensive method adapted by Szymanski, Almeida e Prandini. The excerpts selected from the teachers’ narratives resulted in the definition of seven categories of analysis, aiming at answering the initial question: which school actions can contribute for teachers’ permanence at a state school of São Paulo? Results point to the strong actions of the principal in order to guarantee positive school climate, care, discipline, active family/community participation, school organization, perception of results and collective work